Intermodal-vectorial four-wave mixing processes involving LP01, LP11, LP02 and LP21 modes of birefringent fibers - Tarnowski Karol; Żołnacz Kinga; Majchrowska Sylwia; Urbańczyk Wacław (EPJ Web of Conferences, 2023)
We present the complete (analytical, numerical and experimental) analysis of intermodal-vectorial four-wave mixings proccesses in birefringent fibers. We analyze phase-matching condition and overlap coeffi-cients to indicate possible processes. Then, we demonstrate multiple four-wave mixing processes in LP01 and LP11 modes numerically and experimentally. Finally, we extend theoretical analysis to account higher-order modes: LP02 and LP21.